Vibration effect on laboratory balance with different readability and loading - Intiang, Jittakant; Variyart, Weerachai; Boonsanit, Sompote; Nakkead, Phlapphlueng (Bulletin of Applied Sciences, 2022)
This research is aimed to find the vibration effect on the performance of laboratory balances with different readability and loading in order to propose the guideline for installing the balance in the environment avoiding the vibration effect for ultimate performance. The balances with different readability 0.01 g, 0.001 g, 0.0001 g, 0.00001 g, 0.000001 g and different loading value are investigated. The experimental setup is consisted of the anti-vibration table for installing the balance in order to exclude the vibration from the floor, the exciter used to generate the vibration, and the accelerometer used for detecting the vibration signal. The natural frequency (Hz) of the balance system and the amplitude of vibration which effect to the reading performance of the balances are measured. The results show that most balances (different readability) response to the high frequency (> 400 Hz) except the balance with 0.01 g readability that the natural frequency is 30 Hz which is low frequency the same as the source of vibration in the laboratory; motor of the air-conditioner 30 Hz to 50 Hz. The amplitude of vibration is in the range of 0.3 m/s to 0.7 m/s. Furthermore, the natural frequency of most balances are the same or slightly different at different loading in the range of maximum capacity. Therefore, the loading value is insignificant effect to the natural frequency of the balance system.